Subchronic effect of different doses ofDiclofenac Sodium on female reproductive system in rats. - Bedoor A. Salim; Muhsin S.G. AL-Moziel; Ausama Ayob Jaccob (College of Pharmacy University of Baghdad, 2023)
NSAIDs are widely utilized drugs in today's world. These medications are well-known for their anti-inflammatory and analgesic properties. The goal of this study was to suggest and explain the subchronic effects of low and high doses of diclofenac on female reproductive system in rats. A total of 24 female rats were divided into 4 groups, six rats in each. The first group was given distilled water as a control, the second and third groups were given diclofenac (1 mg/kg) and(5 mg/kg) respectively. The fourth group was given a combination of diclofenac and mefenamic acid for 35 days. Hormonal, biochemical, and hematological tests were performed.  Low dose diclofenac showed no significant change regarding PGE2, LH, progesterone, prolactin, and glutathione, but an increase in FSH, and decrease in estrogen compared to control group were documented. In contrast, high dose diclofenac alone or combined with mefenamic acid showed   significant impact on female reproductive system documented by biochemical and histopathological evaluations. At hematological levels diclofenac decrease RBC,HGB, and platelet account but no change in the total WBC were found. Sub-chronic use of DS alone or in combination with mefenamic acid  have a deleterious impact on the female reproductive system, oxidative stress and hematological parametersKeywords:NSAIDs, diclofenac sodium, female reproductive toxicity, hematologic.